Sulforaphane protects hearts from early injury after experimental transplantation - Li, Zhanqing; Galli, Uwe; Becker, Luis Eduardo; Bruns, Helge; Nickkholgh, Arash; Hoffmann, Katrin; Karck, Matthias; Schemmer, Peter (Annals of transplantation, 2013)
Background: Oxidative stress is a major factor in the development of ischemia reperfusion injury (IRI) after heart transplantation. The isothiocyanate found in broccoli - sulforaphane (SFN) - is an indirect antioxidant that acts by inducing Nrf2-dependent Phase 2 enzymes, such as NAD(P)H-quinone oxidoreductase 1, glutathione reductase, glutathione peroxidase, and the cardioprotective enzymes, haemoxygenase-1 (HO-1) and thioredoxin (Trx-1), participate in adaptive and protective responses to oxidative stress and various inflammatory stimuli. The aim of this study was to ameliorate IRI following heart transplants by recipient preconditioning. Material and Methods: Male Lewis rats were randomly divided into groups of n=10 animals each for heart donation. Heart grafts underwent 18 hours of cold storage in histidine-tryptophanketoglutarate (HTK) solution. Preconditioning of recipients with sulforaphane was performed 24 hours before transplantation. Results:SFN significantly decreased serum levels of TnT, CK, CK-MB, LDH, AST, and ALT, which correlated with better graft function scores and improved survival prognosis. Pretreated recipients showed significantly decreased expression of iNOS, caspase 3, and HIF-1a. Conclusions: Our results indicate that recipient preconditioning with SFN protects the heart from IRI after experimental transplantation.
Gesehen am 24.02.2022
Richtiger Nachname vom 5. Autor: Arash Nickkholgh